Integrating E-Learning into The Vocational High School Curriculum: Strategies, Challenges, and Future Directions - Hakiki, Muhammad; Kartika, Rani; Hamid, Mustofa Abi; Utami, Resti; Suprapto, Yuni; Subhanadri, Subhanadri (Malikussaleh University, Aceh, Indonesia, 2026)
This study investigates the integration of e-learning into the curricula of Vocational High Schools, emphasising strategies, challenges, and prospective avenues for enhancing the quality of teaching and learning. E-learning plays a crucial role in enhancing vocational education within the framework of rapid digital transformation, facilitating flexibility, interactivity, and access to a variety of learning resources. A qualitative approach was employed to collect data through in-depth interviews, surveys, and participatory observation at 39 Vocational High Schools in Padang, Indonesia, which offer Computer and Network Engineering and Software Engineering programs. The research included 73 teachers and 195 students who participated in e-learning activities. The findings indicate that both teachers and students possess favourable views regarding the integration of e-learning, recognising its capacity to improve conceptual understanding, promote learner autonomy, and create more engaging educational environments. Educators indicated that the implementation of learning management systems, online discussions, multimedia resources, and virtual simulations enhances student engagement and fosters collaboration. Data triangulation confirmed that teacher competence and engagement in professional development significantly impact e-learning success. Challenges remain, such as insufficient digital literacy, inadequate infrastructure, and diminished direct interaction. The research highlights the necessity of ongoing teacher training, dependable technological infrastructure, and curriculum redesign in accordance with industry standards to facilitate effective e-learning integration. It is advisable to establish collaborative partnerships among educational institutions, industry stakeholders, and policymakers to improve curriculum relevance and learning outcomes. Ongoing monitoring and evaluation are crucial for sustaining dynamic and adaptive e-learning environments. This study presents a framework aimed at enhancing e-learning implementation in Vocational High Schools, thereby facilitating students' preparedness for the digital and industrial workforce.